INVESTIGATING AGE–BASED COMPLIMENTS IN PERSIAN - Vahid Shahidi Pour; Gholam Reza Zarei (University of Kuningan, 2016)
The present study was an attempt to investigate differences in the use of compliments in Persian across age as a social variable. Data was gathered through a Discourse Completion Task (DCT) with imaginary situations in which 200 native Persian speakers were asked to put themselves in those situations and give compliments. The results indicated that the most frequently used compliment strategies by Persian native speakers were explicit unbound semantic formula and non-compliment strategies. However, the participants used 'other' strategies, future reference, contrast, and request strategies the least. The results also suggested the effect of age on the distribution of compliments. While the younger participants preferred non-compliment strategies the most, the older participants preferred explicit unbound semantic formula strategies the most. However, despite minor differences, all age-groups rarely tended to use future reference, contrast, request, and 'other' strategies. The results cashed light on the cultural and socio-cultural factors affecting the way people offer compliments.Keywords: Pragmatic competence, Speech acts, Compliments, Discourse Completion Task (DCT), Social variables